Вы находитесь на странице: 1из 27

,

2 2012


, , ..

,
(, , , ,
). , T
M(x, y , z)
t,
(, ),

z = f (x, y ), u = g(t, s), z = z(x, y ),


...
u = f (x, y , z), v = v (x, y , z), . . .
n u = f (x1 , x2 , . . . , xn ), . . .

z = f (x, y ), u = g(t, s), z = z(x, y ),


...
u = f (x, y , z), v = v (x, y , z), . . .
n u = f (x1 , x2 , . . . , xn ), . . .

z = f (x, y ), u = g(t, s), z = z(x, y ),


...
u = f (x, y , z), v = v (x, y , z), . . .
n u = f (x1 , x2 , . . . , xn ), . . .

. f (x, y ) = x 2 xy .
f (2, 3) = 22 2 3 = 2,
f (a, 1) = a2 + a,
f (x, x) = 0,
f (a + b, a b) = (a + b)2 a2 + b2 = 2ab + 2b2 .

. f (x, y ) = x 2 xy , h(u, v ) = u v .
f (h(5, 2), 0) = f (3, 0) = 32 2 0 = 9,
f (h(a, a), b) = 0,
f (x, y ) = xh(x, y ), x, y .

. f (x, y ) = x 2 xy .
f (2, 3) = 22 2 3 = 2,
f (a, 1) = a2 + a,
f (x, x) = 0,
f (a + b, a b) = (a + b)2 a2 + b2 = 2ab + 2b2 .

. f (x, y ) = x 2 xy , h(u, v ) = u v .
f (h(5, 2), 0) = f (3, 0) = 32 2 0 = 9,
f (h(a, a), b) = 0,
f (x, y ) = xh(x, y ), x, y .

. f (x, y ) =
x, y .

p
4 x 2 y 2

(x, y ),
f (x, y ), .
D(f ).

. xOy R 2 ( R2 ).
D(f ) 2
.
. z = ln(x + y )
x + y > 0.

. :

D ,
.
D, .
D1 = {x 2 + y 2 4} D2 = {x + y 0} .
C1 = {x 2 + y 2 < 4} C2 = {x + y > 0} .

,
.
D1 C1 , D2 C2 .

f (x, y )
z = f (x, y ).
p
z = R 2 x 2 y 2 .
.

f (x, y ) = C, C
, f (x, y ).
xOy
z = f (x, y ) ,
xOy .
.

z=2
z=1
z = 0.5
x

. : z = ax 2 + by 2

. : z =

xy


.
z = f (x, C) = (x), z = f (C, y ) = (y ), C
.
z = f (x, y ) y = C x = C.


.
,
.

M0 (x0 , y0 ),

> 0 C(M0 , )
> 0 M0 ,
M(x, y ) C(M0 , ) |f (x, y ) f (x0 , y0 )| < .

fx0 (x0 , y0 ) = lim

x0

f (x0 + x, y0 ) f (x0 , y0 )
x

f (x, y ) x
(x0 , y0 ).
-.
(x) = f (x, y0 ) (y0 ).

fx0 (x0 , y0 ) = (x0 ).


, fy0 (x0 , y0 ) = 0 (y0 ), (y ) = f (x0 , y ).
z = f (x, y ):
fx0 (x, y ), fy0 (x, y ), zx0 , zy0 ,
.

z z
,
x y

z = x 2y +

1
,
y
zx0 = 2xy ,

zy0 = x 2

1
y2

z = x arctg xy ,
zx0 = arctg xy +

xy
,
1 + x 2y 2

zy0 =

x2
1 + x 2y 2

u = (as + bt)2
u
= 2(as + bt)a,
s

u
= 2(as + bt)b.
t

z = ax + by + c

z = f (x, y ) = ax + by + c
, .
(x0 , y0 )
z = z0 + a(x x0 ) + b(y y0 ),
z0 = f (x0 , y0 ) = ax0 + by0 + c .
n = (a, b) .
.
.

f (x, y ) M0 (x0 , y0 )
(x0 , y0 ),

q
f (x, y ) = z0 + A(x x0 ) + B(y y0 ) + (x x0 )2 + (y y0 )2 ,
z0 = f (x0 , y0 ), 0, x x0 y y0 .
(
)
A = fx0 (x0 , y0 ), B = fy0 (x0 , y0 ).

,
f (x, y ) z0 + A(x x0 ) + B(y y0 ),

z = z0 + A(x x0 ) + B(y y0 )
z = f (x, y ) (x0 , y0 , z0 ).


, f (x, y )
(x0 , y0 ), z = f (x, y ) f (x0 , y0 )

p
z = Ax + By + x 2 + y 2 ,

, :
dz = df (x0 , y0 ) = Ax + By = fx0 (x0 , y0 )x + fy0 (x0 , y0 )y

dz =

z
z
dx +
dy .
x
y